Evolution of market uncertainty around earnings announcements - Isakov, Dušan; Pérignon, Christophe (Journal of Banking & Finance, 2001)
This paper investigates theoretically and empirically the dynamics of the implied volatility or implied standard deviation (ISD) around earnings announcements dates. The volatility implied by option prices can be interpreted as the level of volatility expected by the market over the remaining life of the option. We propose a theoretical framework for the evolution of the ISD that takes into account two well-known features of the instantaneous volatility: volatility clustering and the leverage effect. In this context, the ISD should decrease after an earnings announcement but the post-announcement ISD path depends on the content of the earnings announcement: good news or bad news. An empirical investigation is conducted on the Swiss market over the period 1989–1998.